2006
DOI: 10.1248/jhs.52.352
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Activity of Atmospheric Ultrafine Particles at a Roadside Site and a Suburban Site

Abstract: 3), although the activity in the fine particle fraction at the roadside site was only 1.4-fold higher than that at the suburban site. These results indicated that, with regard to mutagenicity, the health risk due to ultrafine particles is relatively high at roadside areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
1
0
7
Order By: Relevance
“…Therefore, UFPs are believed to be more harmful than PM 2.5 at the same mass concentration. For example, roadside measurements of nitroarene particles with UFP or accumulation mode particle (particle size, 0.15-0.5 µm) diameters showed that the mutagenicity per unit mass of UFPs was significantly higher (Kawanaka et al, 2006(Kawanaka et al, , 2008. The main sources of UFPs include diesel and gasoline vehicle emissions in urban areas; in particular, many nuclear mode particles (particle size, 0.01-0.03 µm) are emitted from diesel engines (Kittelson, 1998;Geller et al, 2005;Vouitsis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, UFPs are believed to be more harmful than PM 2.5 at the same mass concentration. For example, roadside measurements of nitroarene particles with UFP or accumulation mode particle (particle size, 0.15-0.5 µm) diameters showed that the mutagenicity per unit mass of UFPs was significantly higher (Kawanaka et al, 2006(Kawanaka et al, , 2008. The main sources of UFPs include diesel and gasoline vehicle emissions in urban areas; in particular, many nuclear mode particles (particle size, 0.01-0.03 µm) are emitted from diesel engines (Kittelson, 1998;Geller et al, 2005;Vouitsis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Τα στελέχη του μικροοργανισμού Salmonella typhimurium που χρησιμοποιούνται είναι τα TA98 (Cerna et al, 1999(Cerna et al, , 2000Binkova et al, 2003;Brits et al, 2004;Cassoni et al, 2004;Du Four et al, 2004;Erdinger et al, 2004;Pastorkova et al, 2004;Gilli et al, 2007;Kawanaka et al, 2006Kawanaka et al, , 2008, TA100 (Cerna et al, 1999(Cerna et al, , 2000Binkova et al, 2003;Du Four et al, 2004;Erdinger et al, 2004), YG1041 (Pastorkova et al, 2004), YG1024 (Kameda et al, 2004b;Kawanaka et al, 2008), ενώ χρησιμοποιείται ηπατικός μεταβολίτης (S9) για την ενεργοποίηση της ικανότητας μεταλλαξιγένεσης των οργανικών ενώσεων που περιέχονται στα σωματίδια.…”
Section: δοκιμές μεταλλαξιγόνου δραστικότητας-Ames Testunclassified
“…Όπως φαίνεται από το σχήμα 1.8, η μεταλλαξιγόνος δραστικότητα αυξάνεται με τη μείωση του μεγέθους των σωματιδίων (Pagano et al, 1996;Endo et al, 2003;Kawanaka et al, 2004Kawanaka et al, , 2006, εξαιτίας της περιεκτικότητάς τους σε τοξικές οργανικές ενώσεις (Kawanaka et al, 2004(Kawanaka et al, , 2006de Kok et al, 2006;Claxton and Woodall, 2007).…”
Section: κατά μέγεθος κατανομή της μεταλλαξιγόνου δραστικότητας των αιωρούμενων σωματιδίωνunclassified
See 2 more Smart Citations